Insight as a Therapeutic Aim in Psychological Helping Process - Ramazan Akdogan; Ayse Sibel Turkum (Psikiyatride Güncel Yaklaşımlar, 2014)
In psychological helping process, to gain insight is a very important therapeutic aim in order for client to realize his strengths and competence, and to be more functional in his life. Hence, most of the counseling approaches determine the gain insight for client as a necessity for the counseling process. Insight is an abstract term which points out one's gaining of new knowledge and awareness about his/her strengths and competence which s/he did not have before. Since insight gain is an inner process, it is possible to understand whether the client gained it or not only through observing his behaviors. From this point of view, there is a close relationship between insight and action, and in the process of psychological helping, insight must be taken into consideration together with action. In the counseling process, insight may improve either as a spontaneous or gradual awareness. There are many factors that affect the development of insight and its being functional in the client's life. These factors may cover the personal characteristics of the counselor and the client, their attitudes and behaviors as well as the result of their interactions. [Psikiyatride Guncel Yaklasimlar - Current Approaches in Psychiatry 2014; 6(4.000): 375-388]